Implementation of the E-Sidik Application Program by the Traffic Accident Unit in Handling Traffic Accidents in Trenggalek Police Area - Sadyra Fransisnaugusthy (Indonesian Journal of Police Studies, 2021)
This research is motivated by the handling of traffic accidents at the Trenggalek police station in the investigation and supervision of the leadership of the accident cases that occurred with. This has led to the implementation of an E-Sidik application program to assist Laka Traffic Unit investigators in dealing with and overcoming this. The purpose of this study was to describe the use of the E-Sidik application program at the Trenggalek Police in assisting the Traffic Accident Unit in dealing with traffic accidents that occurred. This research uses a qualitative approach with field research. The research location is in the jurisdiction of the Trenggalek Police. Data collection methods include interviews, observation and document studies. The data validity technique uses triangulation of sources, methods, and time. The data analysis technique uses data reduction, data presentation and drawing conclusions and verification. The results of the study found that in handling traffic accidents there were still various obstacles so that the E-Sidik application program was implemented in the Traffic Traffic Unit. The implementation of the E-Sidik application program has been going well, but there are still several factors that influence the application of the application program. These factors are man (Laka Unit personnel), money (budget), methods (accident handling), materials (implementation materials), machines (infrastructure), and markets (community conditions).